Конституція України та принципи соціальної держави - Лощихін, О.М. (Альманах права, 2012)
Статтю присвячено дослідженню проблем визначення змісту і сутності соціальної держави, притаманних їй принципів і виконуваних функцій. Узагальнено зарубіжний досвід функціонування соціальної державності. Статья посвящена исследованию проблем определения содержания и сущности социального государства, свойственных ему принципов и выполняемых ним функций. Обобщен зарубежный опыт функционирования социальной государственности. The article deals with the investigation of problems arising in the determining a social state’s substance and nature, its inherent principles and the functions performed. It is pointed out, that successful activities of the state in the social field are one of the conditions for the efficient realisation of economical, political and other state functions. Social activities of the state are its activities aiming to provide adequate living standards for each individual and create equal and just opportunities for its personal development. The substance of state’s functions under the social and economic reforms is determined by the new objectives of the modern state in the social sphere, the latter stipulated by the declaration of the social state concept. The principles of the main trends and forms of the regulating impact of the Constitution of Ukraine as a regulatory and legal document of the highest legal effect in the formation, development and reformation of the public relations in the social and economic sphere were examined; their role and substance were analysed. It is being proved that formation and activities of all the institutes of a democratic, legal and social state are directly dependant on the substance of the norms of the Constitution of Ukraine, the efficiency of their realisation. The experience of a social statehood functioning in the newly industrialised nations, where the transition to the market economy and its rapid development were supported by a very active participation of the state, is summarised. It is held that the fundamental transformations in the economic and legal sphere of the contemporary post-socialist nations with all the definiteness address the questions of the necessity of the fundamental revision of the role and place of the state authorities of different levels in the life sustenance system of the society.